2022
DOI: 10.1007/s12325-022-02193-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Brolucizumab in the Treatment of Neovascular Age-Related Macular Degeneration: A Systematic Literature Review and Network Meta-Analysis

Abstract: Introduction A systematic literature review (SLR) and network meta-analysis (NMA) were conducted to evaluate the comparative efficacy of brolucizumab relative to other anti-vascular endothelial growth factor (VEGF) treatments for neovascular age-related macular degeneration (nAMD) at 1 and 2 years, and overall safety and injection frequency of each treatment. Methods An SLR identifying randomized controlled trials (RCTs) published before June 2021 according to a pre-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
3
12
1
Order By: Relevance
“…A systematic literature review and network meta-analysis comparing all anti-VEGF agents, including the most recently approved faricimab, concluded that brolucizumab therapy produces superior retinal thickness reduction with comparable visual outcomes across all molecules at years 1 and 2. 18 This was achieved with the fewest number of injections per year (5.7 injections/year). 18 Our PRN-based study also revealed a comparable injection frequency (4.74 ± [0.75]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic literature review and network meta-analysis comparing all anti-VEGF agents, including the most recently approved faricimab, concluded that brolucizumab therapy produces superior retinal thickness reduction with comparable visual outcomes across all molecules at years 1 and 2. 18 This was achieved with the fewest number of injections per year (5.7 injections/year). 18 Our PRN-based study also revealed a comparable injection frequency (4.74 ± [0.75]).…”
Section: Discussionmentioning
confidence: 99%
“… 18 This was achieved with the fewest number of injections per year (5.7 injections/year). 18 Our PRN-based study also revealed a comparable injection frequency (4.74 ± [0.75]). Despite the lower injection frequency in our real-world data, consistent and sustained morphological improvement was observed throughout the 52-week study period.…”
Section: Discussionmentioning
confidence: 99%
“…Network meta-analyses have indicated that brolucizumab is noninferior to other anti-VEGF agents in functional and structural outcomes 35–37. Furthermore, real-world data from recent studies on people with nAMD and PCV in several countries have corroborated the efficacy shown in the clinical trials.…”
Section: Brolucizumab: Efficacy and Advantagesmentioning
confidence: 93%
“…Age-related macular degeneration (AMD), which is non-exudative or ''dry'' in early stages and may convert to exudative or ''wet'' in later stages (neovascular AMD, nAMD), is characterized by progressive loss of central vision that can become severe [3]. Although nAMD was previously one of the leading causes of blindness in the elderly [3], the use of anti-vascular endothelial growth factor (anti-VEGF) in clinical practice has reduced the incidence of nAMD-associated blindness dramatically [4]. Patients with unilateral late-stage AMD (including both nAMD and dry AMD) are at risk of conversion to macular neovascularization (MNV) in their fellow eye, at rates as high as 38% over 3 years [5].…”
Section: Introductionmentioning
confidence: 99%